Nano-fatliquoring agent berbasis minyak sawit untuk industri penyamakan kulit: Review Study - Atiqa Rahmawati; Heru Budi Susanto; Fadzkurisma Robbika; Baskoro Ajie; Erlita Pramitaningrum (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2026)
The leather tanning industry is currently transforming toward sustainability through the application of nanotechnology. The fatliquoring process is a crucial stage for providing softness and mechanical strength to leather. Palm oil has great potential as a raw material for fatliquoring agents due to its abundant availability and favorable fatty acid composition. This review discusses the development of palm oil-based nano-fatliquoring agents, which covers fabrication techniques via chemical modifications (such as the use of organosilicon), sonochemical (ultrasonic) physical methods, and the stability of Pickering emulsions. Characterization is emphasized on the analysis of droplet size, zeta potential, and leather fiber morphology using SEM/TEM. The advantage of nanotechnology lies in the deeper penetration of droplets into collagen fibers, which not only enhances mechanical properties but also provides additional functions such as UV resistance and antimicrobial activity. Overall, the utilization of palm oil by-products like deodorizer distillate (DD) in a nano-emulsion offers strong future viability for cleaner production in the global leather industry.